2017
DOI: 10.4081/aiua.2017.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy for low risk prostate cancer, oncological and functional medium term outcomes: A three center prospective study

Abstract: Objectives: Analyze the oncologic and functional outcomes in patients affected by low risk prostate cancer underwent prostate cryotherapy. Materiasl and methods: It’s a prospective tricentric study of 434 patients treated with prostate cryoablation for low risk prostate cancer. By low risk we refer to the D'Amico’s risk classification. Two cycles of freezing/thawing are run for each patient following the technique described by Onik. Results: For the 434 patients, the median age was 66 years with a standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…[ 14 , 16 , 17 ] Several studies have shown that the rate of biochemical failure in patients who have been treated with primary whole gland cryotherapy using cryoprobes of 2.4 mm diameter ranged between 15 and 21% during early follow-up in the initial 24 months. [ 15 , 18 , 19 ] In our study, the rate of recurrence at 24 months is 8% in the V-Probe ® group and 10% in the fixed-size ice probe. We believe this may be in part because 48.5% of our cohort consisted of Gleason 6 on pretreatment biopsy.…”
Section: Discussionmentioning
confidence: 45%
“…[ 14 , 16 , 17 ] Several studies have shown that the rate of biochemical failure in patients who have been treated with primary whole gland cryotherapy using cryoprobes of 2.4 mm diameter ranged between 15 and 21% during early follow-up in the initial 24 months. [ 15 , 18 , 19 ] In our study, the rate of recurrence at 24 months is 8% in the V-Probe ® group and 10% in the fixed-size ice probe. We believe this may be in part because 48.5% of our cohort consisted of Gleason 6 on pretreatment biopsy.…”
Section: Discussionmentioning
confidence: 45%
“…Among the 26 studies [23][24][25][26][27][28][29][30][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] included (Table 3…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [21] reported a PSA decrease of 2 ng/mL. Seven studies [25,26,40,44,47,48,50] assessed recurrence rate using the ASTRO Phoenix definition, whereas two studies [27,43] reviewed the rate of positive post-procedural prostate biopsy. The overall recurrence rate ranged from 15.4% to 62% (using the Phoenix definition, from 15.4% to 40.3%), whereas the overall positive recurrence rate by prostate biopsy ranged from 18% to 62% (Table 5).…”
Section: Primary Outcomes In Primary Treatment Studiesmentioning
confidence: 99%
“…Столь сильное ухудшение было также продемонстрировано в исследовании Е. Lucan и соавт. (2019), результаты которого показали прирост количества пациентов с эректильной дисфункцией после криоабляции (65 %) по сравнению с предоперационным уровнем (19,2 %) [25]. По данным литературы, после брахитерапии результаты более благоприятные.…”
Section: Discussionunclassified